Agonist long protocol improves outcomes of vitrified-warmed embryo transfer in repeatedly thin endometrium. Issue 3 (March 2023) - Wang, Peiyu; Yang, Haiyan; Chen, Zhuo; Chen, Ya; Jin, Congcong; Yu, Rong; Lin, Jia; Chen, Qianqian; Huang, Xuefeng
Abstract: Research question: Does follicular stimulation using human menopausal gonadotrophin (HMG) after pituitary down-regulation by a GnRH agonist improve endometrial thickness (EMT) and clinical outcomes of frozen-thawed embryo transfer (FET; using vitrified-warmed embryos) in women with thin endometrium after intensified oestrogen administration (IOA)? Design: This was a retrospective study. A total of 627 patients attempted 683 FET cycles with at least one previous history of thin endometrium. None of the cycles reached over 7 mm EMT after using oral and vaginal oestradiol for more than 21 days (IOA protocol). A total of 129 cycles proceeded with FET, 305 cycles were cancelled, and 249 cycles involved administration of HMG following GnRH agonist pituitary down-regulation (GnRH agonist + HMG protocol) for further endometrial preparation. Results: EMT became significantly greater (7.18 ± 1.14 mm versus 6.13 ± 0.63 mm, P  < 0.001) using GnRH agonist + HMG compared with previous IOA cycles, but this was not related to serum oestrogen concentrations. A total of 213 cycles after the GnRH agonist + HMG protocol proceeded with FET, showing a significantly increased clinical pregnancy rate, implantation rate and live birth rate compared with those after IOA. Conclusions: The GnRH agonist + HMG protocol for endometrial preparation in FET cycles improves EMT in women with a thin endometrium after IOA and showed significantly better clinical outcomes than IOA. The authors suggest that the GnRH agonist + HMG protocol should be used for EMT that is less than 7 mm after there has been no optimal response to IOA.